Curcumin enhances anti-tumor immune response in tongue squamous cell carcinoma - Liao, Feng; Liu, Li; Luo, En; Hu, Jian (Archives of oral biology, 2018)
•Cell lines (Cal 27, FaDu) and animal model (4NQO mice model) were used in this study.•The MTT assay was used to detect cell proliferation.•The Western blotting, immunohistochemistry and immunofluorescence were used to examine the protein expression.•The flow cytometry was performed to determine the number of Treg and MDSC. This study evaluated the role of anti-tumor immune response of curcumin on tongue squamous cell carcinama (TSCC). Cell lines (Cal 27, FaDu) and animal model (4NQO mice model) were uesd in this study. The MTT assay was used to detecte cell proliferation. The Western blotting, immunohistochemistry and immunofluorescence were used to examine the protein expression. The flow cytometry was performed to determine the number of Treg and MDSC. The expression of PD-L1 and p-STAT3Y705 were does-dependently inhibited in Fadu and Cal 27 cell line. The results of in vivo demonstrated that curcumin significantly attenuated tumor growth in 4NQO mice model. The expression of PD-L1 and p-STAT3Y705 were similarly decreased in vivo. Moreover, the anti-tumor immune response was remarkably improved after curcumin treatment through increasing CD8 positive T cells and decreasing Tregs and MDSCs. Curcumin treatment resulted in inhibition of PD-L1 and p-STAT3Y705 expression both in vitro and in vivo. Moreover, the immunosuppressive tumor microenvironment was changed after curcumin treatment. These data suggested that curcumin could effectively promote anti-tumor immune response in TSCC.